The Role of Management Psychology in Forming Attachment and Motivation for Organizational Performance - Bagas Kurniawan; Haula Nur Imama; Hikmatul Maghfiroh; Yusiana Yusiana; Mu’alimin Mu’alimin (Aksara Shofa, 2024)
Management psychology is a management discipline that uses a psychological approach to understand the personality of each person in an organization. Psychological factors influence individual performance, communication patterns, and interactions in the work environment. The aim of this research is to explain the role of managerial psychology in shaping engagement and motivation for organizational performance. This research uses a literature review method from various books, articles and research reports. The results of the literature review conducted show that a supportive work environment can only be built through good leadership practices. Good leadership practices can be identified from how leaders manage communication and interaction patterns to meet the needs and expectations of each individual. These needs and expectations are met through a fair and humane approach to all members, clear career paths, rewards for work performance, quality development programs, objective job evaluations, and follow-up on job evaluation results. Leaders cannot create a comfortable work environment unless they earn the trust and loyalty of members. Trust can only be obtained when leaders care about all their members, are willing to accept opinions and suggestions, and are willing to share experiences with their members.